A Multicenter Retrospective Study of Epithelioid Trophoblastic Tumors to Identify the Outcomes, Prognostic Factors, and Therapeutic Strategies - Liu, Wu; Zhou, Jianwei; Yang, Jie; Huang, Xiufeng (Frontiers in Oncology, 2022)
Background There is no consensus for the management of epithelioid trophoblastic tumor (ETT) up to date. Objective ETT is the rarest form of gestational trophoblastic neplasia (GTN). Our goal was to assess the outcomes and explore the prognostic factors of patients with ETT through this multicenter retrospective analysis and to devise a risk-adapted approach to clinical management. Methods A total of 31 patients were validated as ETT pathologically between January 2004 and June 2021 from three tertiary hospitals. We retrospectively analyzed the characteristics, treatments, outcomes, and prognostic factors. Results Eight patients experienced a recurrence, and 6 patients died of ETT, resulting in a mortality rate of 19.4%. Five patients with stage I disease had a fertility-preserving treatment. Among them, one patient had a full-term delivery, whereas a 23-year-old patient who declined a hysterectomy died of a recurrent disease. Eight patients of extrauterine ETT with isolated pulmonary lesion were at a young age at diagnosis (median: 30.5 vs. 41, p = 0.003) and had a smaller tumor size (median: 2.4 vs. 4.8 cm, p = 0.003) compared with other patients who had a metastatic disease, and none of them died. The multivariate analyses showed that the number of metastases ≥3 [hazard ratio (HR), 28.16, p = 0.003] was the only significant predictor associated with adverse overall survival, while the number of metastases ≥3 (HR 9.59, p = 0.005) and chemotherapy alone (HR 16.42, p = 0.001) were associated with adverse recurrence-free survival. Patients in stage I or with number of metastases <3 had a favorable prognosis, whereas the prognosis of patients whose number of metastases ≥3 remains poor. Conclusions Chemotherapy alone is insufficient for patients with ETT. Surgical procedures are the mainstay of management for ETT patients. Combined surgery and multi-agent chemotherapy are recommended for patients with metastatic disease and localized disease with persistently positive human chorionic gonadotrophin levels after surgery. The number of metastases at ≥3 is the most critical risk factor for ETT.